Factors contributing muslim preferences to participate in cash waqf in Terengganu / Nurul Fatin Ain Zarimi - Zarimi, Nurul Fatin Ain (2017)
The response of Malaysia public towards cash waqf is still lacking. Even though the amount of cash waqf collected is quiet considerable, the response received is still not there (Mohsin,2009). Besides, the existence of cash waqf is not really known to the public, compared to waqf properties. It still needs more effort because a goal to strengthen a waqfas a third sector in Islamic economy still at low level. According to Arshad (201 1), the awareness and understanding of Malaysia public about cash waqf is still low because they only linked it with the construction of mosque and sites for graveyard. Therefore, the factors that contributing public to participate in cash waqf scheme is something interesting to look at. This study deals with several factors namely religious obligation, subjective norm, attitude, behavioural control and benevolence. The primary data collection will be through survey questionnaire and secondary sources such as journal and internet. To see how Muslim's perception towards Cash waqf scheme, a quantitative method had been used in the research. The questionnaires have been distributed to the 200 respondents randomly in Terengganu. The study found that two factors which are religious obligation and benevolence, significant positively towards the Muslim preference in participating cash waqf scheme.